OCCURRENCE OF CARBAPENEMASES AND EXTENDED-SPECTRUM ΒETA-LACTAMASES IN UROPATHOGENIC ENTEROBACTERIACEAE ISOLATED FROM A COMMUNITY SETTING, SETTAT, MOROCCO - Natoubi, Samira; Barguigua, Abouddihaj; Baghdad, Nezha; Nayme, Kaotar; Timinouni, Mohammed; Hilali, Abderraouf; Amghar, Souad; Zerouali, Khalid (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Urinary tract infections (UTIs) are still commonly diagnosed in outpatients as well as in hospitalized patients. In this study, we investigated the prevalence and performed molecular characterization of extended-spectrum-β-lactamases (ESBL) and carbapenemases produced by Enterobacteriaceae isolates that cause community UTIs in Settat city, Morocco. Methods: From January 2012 to December 2013, all uropathogenic community Enterobacteriaceae isolates were collected from the microbiology laboratory of Hassan II Hospital, Settat, Morocco. Antibiotic susceptibility testing was performed as recommended by Clinical and Laboratory Standard Institute. Phenotypic identification of ESBL and carbapenemase producer isolates was confirmed by the double-disk synergy test and the modified Hodge test, respectively. Molecular characterization of β-lactamase genes was performed using polymerase chain reaction (PCR), followed by sequencing of the obtained products. Results: Among 153 isolates, 31 (20.26%) were multi-drug resistant (MDR). Nine strains (5.88%) were ESBL producers, of which Klebsiella pneumoniae (n=5; 20.83%), Escherichia coli (n=3; 3.15%), and Enterobacter cloacae (n=1; 9.09%) species were identified. The results of ESBLencoding gene detection by sequencing revealed the presence of CTX-M-15 (n=9) in association with other β-lactamase genes such as temoneira 1 (n=8) and sulfhydryl variable 1 (n=5). According to the modified Hodge test and PCR, three isolates (1.96%) were positive carry the bla Conclusion: The emergence of MDR uropathogenic Enterobacteriaceae isolates in our community is highly alarming. Strict measures will be required to control the further spread of these uropathogenic isolates. Keywords: Carbapenemase, Enterobacteriaceae, Extended-spectrum-β-lactamases, Moroccan community. OXA-48 gene. <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; letter-spacing: -.15pt;" lang="EN-US">Keywords: Carbapenemase, Enterobacteriaceae, Extended-spectrum-β-lactamases, Moroccan community. Objective: Urinary tract infections (UTIs) are still commonly diagnosed in outpatients as well as in hospitalized patients. In this study, we investigatedtheprevalenceandperformedmolecularcharacterizationofextended-spectrum-β-lactamases(ESBL)andcarbapenemasesproducedby Enterobacteriaceae isolates that cause community UTIs in Settat city, Morocco. Methods: From January 2012 to December 2013, all uropathogenic community Enterobacteriaceae isolates were collected from the microbiology laboratory of Hassan II Hospital, Settat, Morocco. Antibiotic susceptibility testing was performed as recommended by Clinical and Laboratory Standard Institute. Phenotypic identification of ESBL and carbapenemase producer isolates was confirmed by the double-disk synergy test and the modified Hodge test, respectively. Molecular characterization of β-lactamase genes was performed using polymerase chain reaction (PCR), followed by sequencing of the obtained products. Results: Among 153 isolates, 31 (20.26%) were multi-drug resistant (MDR). Nine strains (5.88%) were ESBL producers, of which Klebsiella pneumoniae (n=5; 20.83%), Escherichia coli (n=3; 3.15%), and Enterobacter cloacae (n=1; 9.09%) species were identified. The results of ESBL- encodinggenedetectionbysequencingrevealedthepresenceofCTX-M-15(n=9)inassociationwithotherβ-lactamasegenessuchastemoneira1 <span style="font-size: 8.0pt; line-height: 100%; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <!--[endif]--><!--[if !mso]--> <!--[endif]--> OXA-48 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]> <v:shape id="_x0000_s1026" type="#_x0000_t202" style='position:absolute; left:0;text-align:left;margin-left:514.1pt;margin-top:7pt;width:15.15pt; height:4.65pt;z-index:-1;mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->(n=8) and sulfhydryl variable 1 (n=5). According to the modified Hodge test and PCR, three isolates (1.96%) were positive carry the bla gene. <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Conclusion:TheemergenceofMDRuropathogenicEnterobacteriaceaeisolatesinourcommunityishighlyalarming.Strictmeasureswillberequired to control the further spread of these uropathogenic isolates. <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; letter-spacing: -.15pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Ke<span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">ywords: <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Carbapenemase, Enterobacteriaceae, Extended-spectrum-β-lactamases, Moroccan community.